Influence of Handheld Mobiles on Parotid: A Cohort Study - Gracelin E Ranjitha; Ravi David Austin; Sarvathikari Ramasamy; Chinnappa Saravana Bharathi; Deepthi Angeline; Sakthivel Sambasivam (Wolters Kluwer Medknow Publications, 2017)
Introduction: Mobile phones generate heat and radiofrequency radiation. The parotid gland is one potential target, because mobile phones are pressed against the side of the face where the gland is located. Aims and Objectives: To compare the effect of mobile phone radiation on parotid gland volume, systolic velocity, salivary flow rate, and protein concentration between the dominant and the nondominant side of mobile phone usage among heavy mobile phone users. Materials and Methods: Ultrasonography of the superior lobe of parotid was performed bilaterally to measure gland volume. Systolic velocity of the external carotid artery in gland was calculated bilaterally using color Doppler imaging. Saliva flow rate was measured bilaterally with modified Schrimer strip. Carlson-Crittenden device was used to collect 0.5 ml saliva sample from the duct and biuret assay was done to determine the protein concentration. Settings and Design: A cohort study was conducted with 50 undergraduate students of a dental college based on the inclusion and exclusion criteria. Statistical Analysis Used: Pearson correlation test was used to correlate and compare changes in the parameters of parotid gland and analyzed to a significant level of 0.05. Results: The volume, systolic velocity of blood flow of the external carotid artery, the salivary flow rate, and protein concentration of the parotid gland were significantly more by 11.9, 18, 23, and 8%, respectively, on the dominant side than the nondominant side of mobile phone usage. Conclusion: The study emphasized that prolonged mobile phone usage causes biological changes in parotid gland.